Promoting growth in foreign and second language education: A research agenda for mindsets in language learning and teaching. (November 2019) - Lou, Nigel Mantou; Noels, Kimberly A.
Abstract: Learners' mindsets have received much attention in psychology and education research, but only recently have foreign/second language acquisition (SLA) researchers begun to study these beliefs. Mindsets refer to lay people's beliefs about whether human attributes (e.g., intelligence, personality, language aptitude) are essential, pre-determined traits (fixed mindsets) or malleable propensities can be cultivated (growth mindsets). To encourage more SLA investigations on mindsets, we review existing studies of mindsets in language education to summarize current knowledge and to identify research gaps. We specifically address five questions: (1) What are people's mindsets about language learning ability? (2) How are mindsets linked to other motivational factors? (3) How do contexts influence language mindsets? (4) Do growth-mindset interventions contribute to more adaptive learning, and if so, how? (5) How can educators support students' growth mindset? We highlight that mindsets are systematically associated with various motivational factors in a meaning-making system that guides learners' emotional responses and behavioural acts across different situations. We discuss avenues for future work on whether, why, how, when, for whom, and to what extent mindsets impact different educationally relevant outcomes, including persistence, resilience, and achievement. Understanding these complex questions are important for informing effective education and advancing motivation research in SLA.